Prognostic and therapeutic relevance of IL2RG-related LncRNAs in clear cell renal cell carcinoma - Weijing Hu; Bo Wu; Yongquan Chen; Xiaoling Guo; Xiaosong Wang; Dongwen Wang (Scientific Reports)
Abstract Interleukin-2 Receptor Subunit Gamma (IL2RG) has been implicated in various cancers, but its role in clear cell renal cell carcinoma (ccRCC) remains unclear. This study aimed to explore IL2RG expression, its relationship with IL2RG -related lncRNAs (IRLs). Gene expression and clinical data for ccRCC were obtained from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus(GEO) database. The IRL signature was constructed using Least Absolute Shrinkage and Selection Operator (LASSO) regression analysis. Clinical data validated the diagnostic value of the signature. The prognostic value of the signal was assessed using Kaplan-Meier analysis and Receiver Operating Characteristic (ROC) curves. The prognostic value of the nomogram was further evaluated through calibration curves, ROC curves, and Decision Curve Analysis (DCA). Gene set enrichment analysis (GSEA), single-sample GSEA (ssGSEA), CIBERSORT algorithms, and TISCH2 database were applied to analyze immune function and immune cell infiltration in different risk groups. Clinical treatment differences among populations with varying risks and susceptibilities were predicted using R packages. The expression of IL2RG and key lncRNAs was validated by quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC). IL2RG was significantly upregulated in ccRCC tissues and correlated with advanced clinical stages (p < 0.001). High IL2RG expression was linked to worse overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) (p < 0.05). A 6-IRLs signature was identified, and the resulting model accurately predicted survival outcomes. Immune-related pathways were enriched in high-risk patients, and drug sensitivity analysis indicated that high-risk patients were more responsive to sunitinib and temsirolimus. IL2RG and its related 6-IRLs are potential biomarkers for ccRCC progression. The 6-IRLs model provides a robust tool for predicting prognosis and guiding therapeutic decisions.